The Effect of the Use of Flacing Beam Media on the Ability of the Early Recognition of the Hijaiyah Letters in Children in Paud Mutiara Islam - Lestari, Yuyun Ayu; Ichsan, Ichsan (Universitas Nahdlatul Ulama Surabaya, 2022)
Learning media is a tool that serves to convey learning messages. The media used in this study were 15 colorful stacked blocks with 3 pillars. The purpose of this research is to determine whether there is an effect of using stacking block learning media, so that it can improve the ability to recognize hijaiyah letters in children aged 3 to 4 years at Mutiara Islami PAUD. The research method used is quantitative experiment with One-group Pre-test Post-test Design. This research is a study with one experimental group given treatment (treatment). The treatment carried out in this study consisted of 4 times which showed the results of the pretest with an average of 25.87 in the Undeveloped (BB) category and the Post-Test with an average of 78, 47 with the category of Developing According to Expectations (BSH). This study also tested normality, homogeneity which states that the data are normally distributed and homogeneous. Testing the tcount hypothesis (t-test) with ttable, obtained tcount = 20 from the table with a significant level of = 0.05 and degrees of freedom dk = 14, then the value of t = 2.145, so that tcount > ttable is 20 > 2.145. The results obtained are the rejection of Ho and the acceptance of Ha, which means that there is an influence in the use of stacking block media on the ability to recognize children's early hijaiyah letters. 05 and the degrees of freedom dk = 14, then the value of t = 2.145, so that tcount > ttable is 20 > 2.145. The results obtained are the rejection of Ho and the acceptance of Ha, which means that there is an influence in the use of stacking block media on the ability to recognize children's early hijaiyah letters. 05 and degrees of freedom dk = 14, then the value of t = 2.145, so that tcount > ttable is 20 > 2.145. The results obtained are the rejection of Ho and the acceptance of Ha, which means that there is an influence in the use of stacking block media on the ability to recognize children's early hijaiyah letters